THE IMPACT OF EFFECTIVE TEACHING STRATEGIES ON PRODUCING FAST AND GOOD LEARNING OUTCOMES - Mahmoud Raba, Ahmed Awad Amin (International Journal of Research -GRANTHAALAYAH, 2017)
This study aimed to find out the impact of effective teaching strategies on producing fast and good learning outcomes. It also aimed to determining the role of the study variables (the place graduation, the college where he taught in, the number of published research, the number of conferences and workshops , participation in the Good Samaritan program, teaching experience and academic rank) in producing fast and good Learning outcomes. To achieve these purposes, the researcher used a 25- item questionnaire distributed among lecturers at An-Najah National University. Additionally, the researcher interviewed five lecturers randomly selected from the same faculties at An-Najah National University as well. The data were collected and analyzed using SPSS to answer the questions of the study. The researcher found out that there was positive impact of effective teaching strategies on producing good and fast learning outcomes. Also, the results showed that there were no statistical significant differences at (α = .05) in the impact of effective teaching strategies on producing fast and good learning outcomes due to the study variables. Based on these findings, the researcher recommended the lecturers to use effective teaching strategies via continual improvement and updating their teaching strategies.